Peningkatan Keterampilan Membaca Pemahaman melalui Media Ikan Darat pada Kegiatan Gerakan Literasi Sekolah Siswa Kelas IV A SDN Brawijaya Kecamatan Gunung Puyuh Kota Sukabumi - Sumiati, Yeti (utile: Jurnal Kependidikan, 2018)
This researchpurpose is for increasing reading comprehension skill throughland fish as a media for higher class elementaryschool. This type of research is ClassAct Research (CAR) method with kemmis & Mc. Taggart model, this researchcollaboratively that create collaboration between researcher and class teacher, thisresearch consist of 2 cycle. Participants of this research are 26 IV A (Forth) gradestudents of elementary school and their class teacher as an observer. Collectingtechniques and data analysis that used in this research is using test,observation,fieldnotesand documentation. Result of the researchon the first cycle shown readingcomprehension skill reach 54% finishment this meanit's increasing 46,4% from thepretest result 7,6% finishment. On the cycle II shown that reading comprehension skillreach 100% finishment. Therefore this research shown that with land fish as a media itcould increased reading comprehension skill higher class elementary school.